Case report: Clinical characteristics and treatment of secondary osteoporosis induced by X-linked congenital adrenal dysplasia - Tao, Xiaohui; Xu, Tian; Liu, Li; Lin, Xiaoyun; Zhang, Zhenlin; Yue, Hua (Frontiers in Endocrinology, 2022)
Objective To summarize the clinical features and bone complications in a patient from a large family with X-linked congenital adrenocortical hypoplasia (AHC) and evaluate the efficacy of different treatment regimens on the prognosis of secondary osteoporosis caused by AHC at a 5-year follow-up. Methods A large family with AHC was recruited, and the causative gene mutation was identified by Sanger sequencing in the proband. Clinical features as well as radiological examinations and laboratory indices of osteoporosis secondary to AHC were analyzed in this study. Meanwhile, the proband was treated with classical antiresorptive drugs (bisphosphonates) for 2 years and switched to a vitamin K2 analogue for another 3 years, during which the efficacy of the drugs was evaluated. Results The proband was identified as carrying a homozygous insertion mutation (p. Thr193GlyfsX13) in the NR0B1 (nuclear receptor subfamily 0, group B, member 1) gene, resulting in a premature stop codon due to a frameshift mutation. During treatment and follow-up, the proband did not respond well to bisphosphonate and developed atypical femoral fractures. Vitamin K2 improved clinical symptoms. In terms of bone mineral density (BMD), there is no evidence of any effect of vitamin K2 on the neck of femur, though some minor effects on spinal BMD cannot be excluded. Conclusions Secondary osteoporosis induced by AHC deserves clinical attention. Unlike in primary osteoporosis, the curative effect of bisphosphonates was unsatisfactory and was more likely to cause atypical femoral fractures in long-term treatment. It is suggested that bone anabolic drugs may be better alternatives.